Characterization of the lactation and yield curve in Saanen goats from a dairy farm in the province of Buenos Aires, Argentina (FAVE Sección Ciencias Veterinarias, 2021)
The objective of this study was to determine the productive behavior in Saanen goats by characterizing the lactation curve and the yield according to the number of lactations and the type of delivery in a semi-intensive dairy farm in the province of Buenos Aires. The goat herd was divided into the different categories: first lactation goats (1st L, n = 89); second lactation (2nd L, n = 39), third lactation (3rd L, n = 49); fourth and fifth lactation (4 ° L and 5 ° L, n = 41) and last lactation (UL, n = 38). The type of delivery was classified as Simple (one kid, n = 120) and Multiple (two or more kids, n = 136). The milk control was carried out evaluating the milking twice a day every 42 ± 4 days (BT6 method) by means of mechanical milking with Waikato lactometers. Using a multifactorial analysis of variance, the influence of lactation number and type of delivery on full lactation (PLT) was evaluated. There was a statistically significant difference of the factors (p = 0.0074) and (p = 0.0179) respectively on the PLT. The mean analysis verified significant differences (p
Keywords: Goats; Dairy; Milk control; Saanen